Long-term evaluation of sperm parameters after coronavirus disease 2019 messenger ribonucleic acid vaccination - Parris Diaz, B.S; Alexandra Dullea, M.S; Mehul Patel, M.D; Ruben Blachman-Braun, M.D., M.S; Rohit Reddy, B.S; Kajal Khodamoradi, Ph.D; Emad Ibrahim, M.D; Joginder Bidhan, M.S; Ranjith Ramasamy, M.D (Elsevier, 2022)
Objective: To determine whether the COVID-19 mRNA vaccines can negatively impact the semen parameters of young healthy men in the long-term. Design: We conducted semen analyses on 12 men before, 3 and 9 months after achieving fully vaccinated status. Individuals who admitted a history of infertility or previous azoospermia were excluded from study participation. Subjects: Healthy male volunteers between the ages of 18-50 years old were recruited between September 2021 - March 2022. Main Outcome Measures: Semen analyses were performed and evaluated volume, sperm concentration, total motility, and total motile sperm count (TMSC). The primary outcome was median change in the TMSC at baseline, 3 months, and at least 9 months following vaccination. Results: A total of 12 men volunteered in our study (median age 26 [25 - 30] years). Subjects provided follow-up semen samples at a median of 10 months following the second vaccine dose. There were no significant changes in any semen parameters between baseline, 3 months, and 10 months following vaccination. Baseline samples demonstrated median sperm concentrations and TMSC of 29.5 million/cc [9.3 - 49] and 31 million [4-51.3], respectively. At 9-month follow-up, sperm concentration and TMSC were 43 [20.5 - 63.5] (P=.351) and 37.5 [8.5 - 117.8] (P=.519), respectively. Of note, there were no significant changes in semen volume nor total motility (%) for participants at follow-up. Conclusion: COVID-19 mRNA vaccines and the booster dose does not appear to negatively impact the semen parameters of healthy males up to 10 months following vaccination.